Subsurface Microbial Community Composition in Anchialine Environments Is Influenced by Original Organic Carbon Source at Time of Deposition - Risley, Catherine A.; Tamalavage, Anne E.; van Hengstum, Peter J.; Labonte, Jessica M. (Frontiers in Marine Science, 2022)
Prokaryotes constitute the majority of sedimentary biomass, where they cycle organic carbon and regulate organic matter transformation. The microbes inhabiting sediment are diverse and the factors controlling microbial community composition are not fully understood. Here, we characterized the prokaryotic community using 16S rRNA gene sequencing in 24 stratigraphic layers within a 89 cm (dated to 1900 years old) sediment core from an anchialine sinkhole in the Bahamas with a stratified water column and anoxic bottom water. The microbial community was dominated by members of the Alphaproteobacteria, Dehalococcoidia, Gammaproteobacteria, Bathyarchaeota, and Campylobacter classes. Most interestingly, subsurface microbial community structure could be correlated to previous evidence for timewise changes in the main source of organic matter that was supplied to the sediment accumulating during the last 2000 years, which itself was caused by regional terrestrial vegetation changes. The C:N ratio was correlated to the relative abundance of the microbial classes, and the microbial communities followed three previously determined time periods based on the source of organic matter, which suggests that the carbon source at time of deposition influences the resultant subsurface microbial community composition. These results show that carbon source is a driver of the microbial community composition inhabiting anoxic sediment, which could have implications for improving understanding of carbon cycling in coastal sedimentary basins.

Holocene sedimentation in a blue hole surrounded by carbonate tidal flats in The Bahamas: Autogenic versus allogenic processes - van Hengstum, Peter J.; Winkler, Tyler S.; Tamalavage, Anne E.; Sullivan, Richard M.; Little, Shawna N.; MacDonald, Dana; Donnelly, Jeffrey P.; Albury, Nancy A. (Marine Geology, 2020)
The sediment in North Atlantic blue holes preserves paleoclimate records. However, accurate paleoclimate reconstructions require an improved understanding of allogenic versus autogenic processes controlling blue hole sedimentation. Here we provide a detailed case study of the Holocene stratigraphy within Freshwater River Blue Hole, which is currently surrounded by carbonate tidal flats in the northern Bahamas (Abaco Island). During the Holocene, concomitant coastal aquifer elevation and relative sea-level rise controlled internal blue hole depositional environments. The general Holocene facies succession observed is: (i) basal detrital and freshwater peat, (ii) palustrine to lacustrine marl, (iii) algal sapropel, and finally (iv) bedded carbonate mud. During the middle Holocene when groundwater levels were lower, small changes in accommodation space that were inherited from the bedrock surface below (<1 m) were able to promote significant lateral facies changes. Multiple cores are needed to characterize these lateral facies changes. Hydrographic characteristics of the coastal aquifer (e.g., vertical position, stratification, salinity) relative to the blue hole benthos exert a fundamental control on (a) benthic flora and meiofauna (e.g., charophytes, ostracodes, foraminifera, gastropods) and (b) organic matter production and preservation from pelagic productivity. Over the last 5000 years, water column stratification in Freshwater River Blue Hole was interrupted on millennial to sub-decadal timescales , which are potentially linked to changing aquifer recharge and rainfall. Lastly, historical intense hurricanes passing closely to the west of the site may have promoted deposition of coarse beds at the site. However, the lack of carbonate tidal flat microfaunal remains (foraminifera: Peneroplis) within these coarse intervals indicates that Freshwater River Blue Hole does not preserve a reliable record of hurricane-induced overwash deposition from the carbonate tidal flats during the last 2300 years.
Keywords: Carbonate tidal flats; carbonates; North Atlantic Bahamas; sinkhole

Drought in the northern Bahamas from 3300 to 2500 years ago - van Hengstum, Peter J.; Maale, Gerhard; Donnelly, Jeffrey P.; Albury, Nancy A.; Onac, Bogdan P.; Sullivan, Richard M.; Winkler, Tyler S.; Tamalavage, Anne E.; MacDonald, Dana (Quaternary Science Reviews, 2018)
Intensification and western displacement of the North Atlantic Subtropical High (NASH) is projected for this century, which can decrease Caribbean and southeastern American rainfall on seasonal and annual timescales. However, additional hydroclimate records are needed from the northern Caribbean to understand the long-term behavior of the NASH, and better forecast its future behavior. Here we present a multi-proxy sinkhole lake reconstruction from a carbonate island that is proximal to the NASH (Abaco Island, The Bahamas). The reconstruction indicates the northern Bahamas experienced a drought from ∼3300 to ∼2500 Cal yrs BP, which coincides with evidence from other hydroclimate and oceanographic records (e.g., Africa, Caribbean, and South America) for a synchronous southern displacement of the Intertropical Convergence Zone and North Atlantic Hadley Cell. The specific cause of the hydroclimate change in the northeastern Caribbean region from ∼3300 to 2500 Cal yrs BP was probably coeval southern or western displacement of the NASH, which would have increased northeastern Caribbean exposure to subsiding air from higher altitudes.

Organic matter sources and lateral sedimentation in a Bahamian karst basin (sinkhole) over the late Holocene: Influence of local vegetation and climate - Tamalavage, Anne E.; van Hengstum, Peter J.; Louchouarn, Patrick; Molodtsov, Sergey; Kaiser, Karl; Donnelly, Jeffrey P.; Albury, Nancy A.; Fall, Patricia L. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2018)
Karst basins (e.g., blueholes, sinkholes) accumulate well-preserved sedimentary successions that provide transformative paleoclimatic and paleoenvironmental information. However, the sedimentary processes within these basins are not yet fully understood. Here we present stable carbon isotopic values (δ13Corg) and C:N ratios of bulk organic matter in well-dated sediment cores from Blackwood Sinkhole (Abaco, The Bahamas) to investigate the changing flux of organic matter into the sinkhole during the late Holocene. The provenance of preserved organic matter changed through the late Holocene between three primary sources, as determined by three-endmember mixing modeling: wetland organic matter from the adjacent epikarst surface, authigenic primary productivity in the oligohaline meteoric lens, and terrestrial organic matter from the surrounding landscape. Expansion of wetlands on the adjacent epikarst surface played a critical role by increasing the flux of wetland organic matter to the sinkhole, especially during the last 1000 years. Hurricanes and regional rainfall may have mediated organic matter delivery to the benthos, either through hampering wetland development (prior to 1000 cal yr BP) or by changing dissolved nutrient concentrations available in the basin for primary producers. These results demonstrate that organic matter provenance in karst basins is not constant through time, and is significantly dependent upon both landscape vegetation on the epikarst surface and changing hydrographic conditions that impacts nutrient availability to primary producers.
Keywords: Caribbean; Karst; Mixing model; Stable isotopes; Subtropical landscape